HUBUNGAN INTENSITAS PENYAKIT KARAT DENGAN PRODUKTIVITAS TANAMAN KEDELAI (Glycine max (L.) Merr.) PADA BEBERAPA VARIETAS BERBEDA - Maman Maman; Juni Safitri Muljowati; Rochmatino Rochmatino (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
The severity of plant disease is closely related to the development of the disease itself, including rusts caused by pathogenic fungi. This research aimed to determine the difference of rusts disease severity and to determine the correlation between rusts disease severity with the productivity of different varieties of soybean. The material used was inoculum of rusts pathogenic fungi, Phakopsora pachyrhizi Syd., and four varieties of soybean, i.e., Slamet, Lokon, Bromo, and Ringgit. This research was a split-plot design experimental with subplot was four different varieties of soybean, and the main plot was the control without the treatment of inoculation (In0). The spores suspension density of inoculum of P. pachyrhizi Syd applied was 104 spores/ml (In1). The main parameters observed in this study were the height of plants, the number of pods per plant, the number of seeds per plant, the wet and dry weight of the plant, and the total weight of 100 grains seed. The supporting parameters were the disease severity, the soil acidity, the humidity, and the air temperature. The results showed the plant with lowest rusts disease severity was Slamet variety (18,38%), and the highest was Ringgit variety (35,92%). The correlation test showed the increment of rusts disease severity reduced the number of pods and dry weight of the plant in Lokon variety.